Estudo da propagação de trincas por fadiga em caçambas de recuperadoras de minério - Warley Lopes Moreira (2018)
As reclaimers are extremely used in the mining process, their maintenance costs are high. A frequent failure mode, according to maintenance data, is the occurrence of cracks that can lead to fracture. This problem has been solved by maintenance by welding the damaged parts. The root cause of the failure, however, has not been attacked, which has caused little effectiveness in solving the problem. The objective of this work is to study the fatigue crack propagation velocity of ASTM A572 steel, a material commonly used to manufacture buckets of reclaimers. For the development of the study, a non-destructible test (ultrasound) was performed to identify and determine the growth value of a crack, after N cycles of known work, of a bucket in operation. At second moment, fatigue tests were performed in the laboratory. The test specimens were made of material extracted from the bucket in service. From the data and results of the laboratory tests it was possible to determine the equations and graphs correpondent to the crack size (a) versus number of cycles (N) and crack propagation velocity (da / dN) versus factor strêss concentration (ΔK). The results obtained in the in-service bucket tests were compared with the laboratory test results and the difference between them is perfectly acceptable and justifiable. Due to the good approximation of the results, the characteristic fatigue parameters (C) and (m) obtained for the studied material can be used for life predictions of parts and components of machines and establish reliable data that can support planning of the maintenance and planning of supplies of materials and services.